Biopharmaceutical: an industrial perspective - Walsh, Gary; Murphy, Bredan (New Delhi Springer, 2009)
Biopharmaceuticals, an Industrial Perspective provides a unique and up-to-date insight into the biopharmaceutical industry. Largely written by industrial authors, its scope is multidisciplinary. Several chapters overview the production and medical applications of specific biopharmaceuticals. Other chapters detail additional relevant issues, including the stabilisation of biopharmaceutical products, EU biopharmaceutical regulatory affairs and biopharmaceutical patent law. A series of four chapters reviews important validation issues as applied to biopharmaceutical manufacturing. Additional issues considered include biopharmaceutical information technology as well as viral and non-viral gene therapy. The book is of particular relevance to scientists and allied professionals already employed in the biopharmaceutical industry, or to those seeking employment within this industry. Its scope also renders it an ideal reference source for students undertaking advanced undergraduate or postgraduate courses in biotechnology, pharmaceutical science, biochemistry or medicine.
Keywords: BIOPHARMACEUTICS/PHARMACODYNAMICS/PHARMACOKINETICS; PHARMACEUTICS